Recent Advances in Pupillometry - Rattan, Yamini; Girgla, Kawalinder Kaur; Prasher, Pawan; Mahajan, Gaurav (New Advances in Medicine and Medical Science Vol. 1, 2023)
Importance of pupil analysis within the clinical setting has been extensively employed in patient management and was performed manually in the past. However, manual pupillary assessment can be associated with vital inaccuracies and inconsistencies and previous studies have shown significant inter-examiner disagreement within the manual analysis of pupillary reaction thus affecting the decision making in crucial clinical situations. Recently, automated pupillometry has been proposed as a device for objective, quantitative and repeatable measurements of pupillary reaction, size and symmetry to avoid the bias in manual assessment.Quantitative pupillometry can be used to create a normal database that can provide clinicians with the information needed to manage the patients as well as help determine the need for an immediate referral to an ophthalmologist. In addition to discussing the pupillary light reflex graph and its neural basis, this review article provides an overview of pupillometry. Also, a comprehensive list of the pupil parameters that various quantitative pupillometry devices can measure has been presented. The article concludes with an update on recent developments in pupillometry applications across a variety of fields.